If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -1(8x + -9) = 45 Reorder the terms: 12x + -1(-9 + 8x) = 45 12x + (-9 * -1 + 8x * -1) = 45 12x + (9 + -8x) = 45 Reorder the terms: 9 + 12x + -8x = 45 Combine like terms: 12x + -8x = 4x 9 + 4x = 45 Solving 9 + 4x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4x = 45 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 45 + -9 4x = 45 + -9 Combine like terms: 45 + -9 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 6x-7x+2=12 | | 2x-8+10=3x-7 | | 5*sin(14x)=5*cos(7x) | | 13x^2-8x-20=0 | | -2y+9x=3 | | -14+74=-5(x+3) | | 3y^2-4=y | | 2(4z+2)-6=70 | | 3(t+2)=7(7-t)-9 | | 3x-4x+5=54 | | 3m+6=37 | | 12-2a=18 | | 4.75=1.75+1a | | 20X+32=0 | | 60=32-4(x-3) | | 3x+4z=13 | | x=16+5n | | -3y=15-2x | | -20=-x/10 | | 7(3n-1)=(2n+8)+6 | | X+7=105 | | -x=-140 | | x-5=5n+11 | | Q=3xz-6 | | .6t+7=-8 | | 32+-1t=-1 | | -3-4m+9m=12 | | T-(-5)=5 | | 3(X-3)(X-1)(X-4)+2(X-2)(X-1)(X-4)-4(X-2)(X-3)(X-4)-1(X-2)(X-3)(X-1)=0 | | 3(4y-3)-4=4(5y-6)+7 | | 32-t=-1 | | 15-4x+17=12 |